Ghost stories : classic tales of horror and suspense - Morton, Lisa, 1958-; Klinger, Leslie S (Pegasus Books, 2019)
The ghost story has long been a staple of world literature, but many of the genre's greatest tales have been forgotten, overshadowed in many cases by their authors' bestselling work in other genres. In this spine-tingling anthology, little known stories from literary titans like Charles Dickens and Edith Wharton are collected alongside overlooked works from masters of horror fiction like Edgar Allan Poe and M. R. James. Acclaimed anthologists Leslie S. Klinger (The New Annotated Sherlock Holmes) and Lisa Morton (Ghosts: A Haunted History) set these stories in historical context and trace the literary significance of ghosts in fiction over almost two hundred years<U+2014>from a traditional English ballad first printed in 1724 through the Christmas-themed ghost stories of the Victorian era and up to the science fiction<U+2013>tinged tales of the early twentieth century.